Design and Construction of a Website-Based Village Service System with Chatbot Integration Using the Extreme Programming Method (Case Study: Wonorejo Village, Sumbergempol) - Dea Preciosa Santyana Putri; Mohamad Khoirul Ansor; Joko Iskandar (Jurnal Teknologi Informatika dan Komputer, 2026)
Public services at the village level are the spearhead of government services closest to the community. However, most villages in Indonesia still rely on manual systems for administrative management, including the process of submitting certificates, recording citizen data, and delivering information. Administrative services in Wonorejo Village, Sumbergempol District, are still carried out manually, causing various obstacles, such as inefficiency, long queues, service delays, and limited access to information for residents. This study aims to design and build a website-based village service system integrated with a chatbot to improve the effectiveness and efficiency of administrative services. The system was developed using the Extreme Programming (XP) method through two development iterations, utilizing the PHP-based Laravel framework, MySQL as the database, and Dialogflow as the Natural Language Processing (NLP) platform for the chatbot. The system's main features include online letter submission, application status monitoring, village information management, and an interactive chatbot. Functional testing was conducted using the black box testing method, while user acceptance was measured through a User Acceptance Test (UAT) using an ISO 25010-based instrument involving 12 respondents. The UAT results showed a satisfaction percentage of 95%, included in the very good category. The developed system has proven capable of supporting the digital transformation of public services at the village level.